2012
DOI: 10.5851/kosfa.2012.32.6.713
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Inactivation of Sodium-Habituated Staphylococcus aureus in Ready-to-Heat Sauces

Abstract: The objective of this study was to evaluate the effect of sodium habituation on thermal resistance of Staphylococcus aureus in various ready-to-heat (RTH) sauces. The strain mixture of S. aureus strains KACC10768, KACC10778, KACC11596, KACC13236 and NCCP10862 was habituated up to 9% of NaCl. The inocula of NaCl-habituated and nonhabituated S. aureus were inoculated in 5 g portions of pork cutlet, meat and Carbonara sauces at 7 Log CFU/g, and the samples were vortexed vigorously. The inoculated samples were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A study by Oscar [7] showed that previous exposure of Salmonella to NaCl affected the kinetic parameters of the bacteria, such as lag phase duration and maximum specific growth rate. For Staphylococcus aureus , exposure to NaCl increased its thermal resistance in ready-to-heat sauces [8]. Other studies also showed that the exposure of bacteria to sublethal stresses such as acid, heat, and NaCl increased their cross-protection responses, especially following continuous exposure to the stresses [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Oscar [7] showed that previous exposure of Salmonella to NaCl affected the kinetic parameters of the bacteria, such as lag phase duration and maximum specific growth rate. For Staphylococcus aureus , exposure to NaCl increased its thermal resistance in ready-to-heat sauces [8]. Other studies also showed that the exposure of bacteria to sublethal stresses such as acid, heat, and NaCl increased their cross-protection responses, especially following continuous exposure to the stresses [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…The exposure to sub-lethal stresses, such as acid, heat, salt, and various preservatives, can modify the response to subsequent other stresses, with a mechanism known as cross-protection or cross-resistance response (Beales, 2004;Koutsoumanis, Kendall, & Sofos, 2003). S. aureus treated in Carbonara and meat sauces at 70 C, after an initial decline (about 3e4 log units), reached a constant concentration throughout all the treatment period, with a higher survival ratio if the cells were NaCl pre-habituated (Park et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that exposure to NaCl can influence the adaptive survival and virulence of pathogenic bacteria. The relevance of this has been shown in Salmonella enterica serovar Typhimurium (12) , Staphylococcus aureus (Park et al., ), and Listeria monocytogenes (Garner, James, Callahan, Wiedmann, & Boor, ), whereby bacteria cultured in medium‐containing high NaCl show increased heat tolerance (Park et al., ; Yoon, Park, Oh, Choi, & Yoon, ), antibiotic resistance (Yoon et al., ), and invasion ability into host cells (Garner et al., ; Yoon et al., ). Our previous study also showed that B. pseudomallei grown under salt stress displayed significantly greater resistance to the antibiotic ceftazidime (Pumirat et al., ).…”
Section: Introductionmentioning
confidence: 99%